(untitled) (Herald of Journalism, 2020)
The article studies traditional the arts and nature of the modern figura tive arts and considers personal formation of art language. By analyzing creations of the Kazakh painters we are assured that that the nature of the Kazakh figurative arts passes a stage of the traditional genetic interrelation and modern times of the world figurative arts. The feature of similarities of the artistic language with the form of the world and Kazakh traditional world views is revealed in creations of distinguished painters of the Kazakh and world arts such as A.Sydykhanov, E.Tolepbai.